PENGETAHUAN IBU TENTANG PEMBERIAN VITAMIN A PADA BALITA (Al-Asalmiya Nursing: Jurnal Ilmu Keperawatan (Journal of Nursing Sciences), 2024)
Vitamin A is an important fat-soluble nutrient stored in the liver, but cannot be synthesized by the human body and must be absorbed from outside the body. This vitamin affects eye health/vision, and growth and  strengthens the immune system. The normal need for vitamin A for adult women is 700 micrograms/day and for men 900 micrograms/day.  The children need 300 to 900 micrograms/day, pregnant women 770 micrograms/day, and breastfeeding women 1300 micrograms/day. Deficiency of vitamin A intake can cause night blindness due to disruption of the regeneration process of visual pigment in the retina. If this condition is left for a long time, the cells in the retina will degenerate, and xerophthalmia will occur which will result in permanent blindness. Other than that, vitamin A deficiency also causes xerosis and damage to the mucous membranes of the intestines and lungs, as well as body decline. Because of the importance of vitamin A intake, this research aimed to determine the description of mothers' knowledge about giving vitamin A in Bregan Muryodadi Bambanglipuro. The research results showed that the level of knowledge and attitudes of mothers regarding giving vitamin A was good knowledge 33%, sufficient knowledge 52%, and poor knowledge 15%. So, it can be concluded that most mothers in Bregan Hamlet, Mulyodadi, and Bambanglipuro have sufficient knowledge (52%) about giving vitamin A.
Keywords: Pengetahuan; Vitamin A; Ibu; Balita